Chemical components analysis of handmade alcoholic beverages with special focus on psychoactive drugs as adulterants - Morvarid Sadat Miri; Dariush Badakhshan; Maryam Akhgari; Masoud Ghadipasha (MethodsX)
Handmade alcoholic beverages are produced in clandestine laboratories. There are reports concerning the of counterfeit alcoholic beverages adulterated with psychoactive drugs. The purpose of this study should be to analyze volatile components and psychotropic substances in handmade alcoholic beverages. In this study, 616 samples were analyzed for the detection of ethanol, methanol, isopropanol, and acetone using gas chromatography. High-performance liquid chromatography was used for the analysis of benzodiazepines, nicotine, morphine, codeine, methadone, tramadol, and methamphetamine. Results were analyzed statistically by SPSS 25 and EXCEL 16 software. These beverages are sold in Iranian drug black market without regulatory and market oversight with increased risk of safety issues. In conclusion, it is important to know the drug profile in alcoholic beverages to investigate the cause and manner of poisoning with these kinds of fake beverages. • Ethanol was found in 86 % of the samples, while methanol, a toxic contaminant, was present in 8 %. • Several psychotropic substances, including methadone, tramadol, morphine, codeine, nicotine, benzodiazepines, and methamphetamine, were identified, showing intentional adulteration. The most common adulterants were methadone (24 %), diazepam (16.1 %), and tramadol (13.8 %). • Furthermore, 36.8 % of adulterated samples contained at least one benzodiazepine, reflecting widespread tampering in alcoholic beverages.